Application of Antagonistic Microorganisms for the Biocontrol of Yellow Leaf Blotch on Vandaceous Orchid Caused by Pseudocercospora dendrobii - Kongraem, Natthawadee; Intanoo, Wanwilai (Thai Agricultural Research Journal, 2023)
The efficacy of cell suspensions and culture filtrate of Bacillus amyloliquefaciens, B. cereus and spore suspensions of Trichoderma asperellum strain CB-Pin-01 were tested in inhibiting spore germination of Pseudocercospora dendrobii, the causal agent of yellow leaf blotch on Vanda orchids at 24 hrs. The result showed that the antagonistic microorganisms were able to inhibit the germination of P. dendrobii spores by 85.38 - 99.74% and shorten the germ tube growth compared to the control treatment. Spore suspension of T. asperellum strain CB-Pin-01 and cell suspension of B. amyloliquefaciens were the most effective in inhibiting germ tube germination at 99.74% and 99.30% while germination inhibition percentages of culture filtrate of B. cereus, T. asperellum strain CB-Pin-01, B. amyloliquefaciens and B. cereus cell were 95.13, 89.83, 86.61 and 85.38%, respectively. Spraying of the 3 antagonistic microorganisms on diseased orchid leaves during the rainy season resulted in significant reduction of disease incidence 7 days after the application compared to the control treatment. B. cereus contributed to the smallest lesion size of 0.01 mm, followed by B. amyloliquefaciens of which lesion size was 1.34 mm, while the size of the lesion in the control treatment was 8 mm. Treatments of folpet and T. asperellum strain CB-Pin-01 showed the lesion sizes of 5.34 and 3.34 mm, respectively.